Peningkatan Kemampuan Servis Bawah Bola Voli Melalui Metode Pembelajaran Team Games Tournamen (TGT) - Rachmat Permadi; Sisworo Sisworo; Suratman Suratman (Journal of Sport Coaching and Physical Education, 2024)
The purpose of this research is to find out whether the Teams Games Tournament (TGT) learning model influences volleyball learning outcomes in class X SMA Negeri 10 Semarang. This type of research is classroom action research (PTK) in the form of quantitative research. The subjects in this research were all students in class X-1 of SMA Negeri 10 Semarang, totaling 34 students, consisting of 11 male students and 23 female students. The results of data processing show that there were 3 students (9%) who completed the action before the action or pre-cycle, after being given the action in cycle I, there was an increase in the completion of learning outcomes to 16 students (47%). Then there was an increase in the completeness of learning outcomes in cycle II, namely as many as 28 students completed it or 82%. So, it is concluded that there is an influence of the Teams Games Tournament (TGT) learning model on volleyball learning outcomes in class X students at SMA Negeri 10 Semarang. Result of this Study, TGT can increase the students learning outcomes. TGT Methode should be implemented in other games like volleyball.